USE OF INTERNATIONAL EXPERIENCE IN IMPROVING LEGAL PRACTICE AND ITS APPLICATION IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2023)
This dissertation is devoted to the study and analysis of the international experience of the United States, Germany, and China in the field of enhancing legal advocacy and its application in the context of the Republic of Uzbekistan. The objective of the research is to identify effective methods, principles, and practices employed in other countries with the aim of improving the work of legal advocacy, as well as to determine the feasibility and appropriateness of their implementation within the national legal advocacy system in Uzbekistan. The research will involve an analysis of the organizational and legal structure of the legal advocacy institution in the United States, Germany, and China, including their legislative foundations and operational mechanisms. The obtained results will enable the identification of prospective directions and recommendations for the enhancement of legal advocacy in Uzbekistan, taking into account the best international practices